An mRNA-based workflow validating neo-epitope presentation through HLA-I/peptide affinity purification - Esprit, Arthur; Autaers, Dorien; Thielemans, Kris; Pepermans, Elise; Boonen, Kurt; Baggerman, Geert; Franceschini, Lorenzo; Breckpot, Karine (Frontiers in Immunology, 2025)
Presentation of human leukocyte antigen (HLA)-class I-restricted neo-epitopes is key for inducing an adaptive cytotoxic T-lymphocyte response against cancer. Validating presentation of these cancer-specific neo-epitopes following delivery to antigen-presenting cells (APCs) is critical to advance personalized therapeutic cancer vaccines. Current workflows for neo-epitope identification are often laborious and depend on computational deconvolution to determine the correct peptide sequence and its corresponding restriction element. We evaluated an mRNA-based workflow for more precise purification of HLA-I-peptide (pHLA)-complexes, facilitating peptide identification by liquid chromatography-tandem mass spectrometry (LC-MS/MS). This approach uses mRNA encoding a specific HLA-I-molecule fused to a Twin-Strep-Tag (HLA-TST), allowing affinity-based purification and downstream analysis of pHLA-complexes. As a proof-of-concept, we co-electroporated mRNA encoding TST-HLA-A*02:01 and mRNA encoding an HLA-A*02:01-restricted epitope in HLA-A*02:01-negative APCs. We demonstrated successful purification and detection of the delivered epitope via LC-MS/MS. These findings highlight the potential of the mRNA-based workflow to verify neo-epitope presentation by APCs. Still, further investigation is necessary to fully understand the technical variables that can influence peptide identification by LC-MS/MS.